2023
DOI: 10.1002/rrq.511
|View full text |Cite
|
Sign up to set email alerts
|

Is a Phone‐Based Language and Literacy Assessment a Reliable and Valid Measure of Children's Reading Skills in Low‐Resource Settings?

Shauna‐Marie Sobers,
Hannah L. Whitehead,
Konan Nana Anicet N'Goh
et al.

Abstract: Technology‐based remote research methods are increasingly widespread, including learning assessments in child development and education research. However, little is known about whether technology‐based remote assessments remain as valid and reliable as in‐person assessments. We developed a low‐cost phone‐based language and literacy assessment for primary‐school children in low‐resource communities in rural Côte d'Ivoire using voice calls and SMS. We compared the reliability and validity of this phone‐based ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
4
1
Order By: Relevance
“…One notable finding within the current work is the insignificant effect of vocabulary. In the current study, vocabulary was not predictive of literacy, contrary to previous work in Côte d'Ivoire using the same task (Sobers et al, 2023). The vocabulary measure, an antonym generation task, consisted of five items (α = .61) and had comparable reliability to a 10-item version (previously used with primary school children in Côte d'Ivoire (α = .63)).…”
Section: Vocabularycontrasting
confidence: 97%
See 1 more Smart Citation
“…One notable finding within the current work is the insignificant effect of vocabulary. In the current study, vocabulary was not predictive of literacy, contrary to previous work in Côte d'Ivoire using the same task (Sobers et al, 2023). The vocabulary measure, an antonym generation task, consisted of five items (α = .61) and had comparable reliability to a 10-item version (previously used with primary school children in Côte d'Ivoire (α = .63)).…”
Section: Vocabularycontrasting
confidence: 97%
“…LITERACY NUMERACY COVARIANCE been found to predict literacy in this population (Ball et al, 2022;Jasińska et al, 2022b). We investigated the reliability and validity of language and literacy tasks in this population in a separate manuscript (Sobers et al, 2023). We found the 10-item version of the task was fairly reliable (α = .63) and valid (i.e., correlated with other language measures and predicted reading performance); we also replicated the analysis with a five-item version and found similar reliability and validity (see osf.…”
Section: E105mentioning
confidence: 99%
“…For example, Yeatman et al ( 2021) developed a browser-based word reading assessment with a strong correlation (r = .86) with a standardized paper-based reading test (Letter-Word Identification from Woodcock-Johnson; Woodcock et al, 2001). Similarly, Sobers et al (2023) reported that their cell phone-based remote assessments evaluating several aspects of language and literacy showed moderate to strong correlations (rs = .35-.80) with traditional paper-based assessments. While our studies examined handwriting skills, the correlations between OAHaS and the paper-based writing test were comparable to those reported for these online language and reading assessments.…”
Section: Psychometric Properties and Practical Utilitymentioning
confidence: 94%
“…To date, only a handful of online assessments of language and literacy have established reliability and validity (e.g., Hulme et al, 2024;Sobers et al, 2023;Yeatman et al, 2021). For example, Yeatman et al ( 2021) developed a browser-based word reading assessment with a strong correlation (r = .86) with a standardized paper-based reading test (Letter-Word Identification from Woodcock-Johnson; Woodcock et al, 2001).…”
Section: Psychometric Properties and Practical Utilitymentioning
confidence: 99%
“…mouli or bape) as they could in 60 seconds for each task. These measures have been previously utilised in Côte d'Ivoire, and have been found to be both reliable and valid in this population (Sobers et al, 2023).…”
Section: Egra Literacy Taskmentioning
confidence: 99%